Diversity of photoreceptor arrangements in nocturnal, cathemeral and diurnal Malagasy lemurs. Issue 1 (10th March 2017) - Peichl, Leo; Kaiser, Alexander; Rakotondraparany, Felix; Dubielzig, Richard R.; Goodman, Steven M.; Kappeler, Peter M.
Abstract: The lemurs of Madagascar (Primates: Lemuriformes) are a monophyletic group that has lived in isolation from other primates for about 50 million years. Lemurs have diversified into species with diverse daily activity patterns and correspondingly different visual adaptations. We assessed the arrangements of retinal cone and rod photoreceptors in six nocturnal, three cathemeral and two diurnal lemur species and quantified different parameters in six of the species. The analysis revealed lower cone densities and higher rod densities in the nocturnal than in the cathemeral and diurnal species. The photoreceptor densities in the diurnal Propithecus verreauxi indicate a less "diurnal" retina than found in other diurnal primates. Immunolabeling for cone opsins showed the presence of both middle‐to‐longwave sensitive (M/L) and shortwave sensitive (S) cones in most species, indicating at least dichromatic color vision. S cones were absent in Allocebus trichotis and Cheirogaleus medius, indicating cone monochromacy. In the Microcebus species, the S cones had an inverse topography with very low densities in the central retina and highest densities in the peripheral retina. The S cones in the other species and the M/L cones in all species had a conventional topography with peak densities in the central area. With the exception of the cathemeral Eulemur species, the eyes of all studied taxa, including the diurnal Propithecus, possessed a tapetum lucidum, a feature only found among nocturnal and crepuscular mammals. Abstract : Retinal cone photoreceptor arrangements were studied in 11 species of Malagasy lemurs. The diversity of cone patterns ranges from relatively high cone densities and the presence of medium‐to‐longwave‐sensitive (green) as well as shortwave‐sensitive cones (magenta) in the diurnal sifaka (top) to low cone densities and an absence of shortwave‐sensitive cones in the nocturnal dwarf lemurs (bottom).